3D inkjet printing of star block copolymer hydrogels cross-linked using various metallic ions. Issue 88 (7th December 2017) - Nakagawa, Y.; Ohta, S.; Nakamura, M.; Ito, T.
Abstract : We have, for the first time, investigated 3D inkjet printing of ionically cross-linked star block copolymer hydrogels. Abstract : Novel precursor polymers for three-dimensional (3D) inkjet printing of hydrogels are required for various biomedical applications. We have, for the first time, investigated 3D inkjet printing of ionically cross-linked star block copolymer hydrogels, for which the precursor polymer has a dendritic polyester core, a poly(oligo(ethylene glycol) methyl ether acrylate) inner layer, and a poly(acrylic acid) outer layer. The star block copolymer solution (8.0 wt%) showed a viscosity of 7–8 mPa s, which is suitable for inkjet printing. This solution formed a homogeneous hydrogel upon the addition of metallic ions, such as the zinc, copper(ii ), aluminum, and ferric ion. The elasticity of the resulting hydrogels was dependent on the ion species. The rapid sol–gel transition induced by the metallic ions enabled 3D inkjet printing of the star block copolymer hydrogels, through ejection of the star block copolymer solution and subsequent ionic cross-linking to achieve layer-by-layer deposition of the gelled droplets.